Diurnal and exercise-related variability of Haemoglobin and Reticulocytes in athletes - Schumacher, Y. O.; Wenning, M.; Robinson, N.; Sottas, P.-E.; Ruecker, G.; Pottgiesser, T. (International Journal of Sports Medicine, 2010)
Haemoglobin (Hb) and Reticulocytes (Ret) are measured as indirect markers of doping in athletes. We studied the diurnal variation, the impact of exercise, fluid intake and ambient temperature in athletes on these parameters. Hourly venous blood samples were obtained from 36 male athletes of different disciplines (endurance (END) and non-endurance (NON-END)) over 12 h during a typical training day. Seven inactive subjects served as controls (CON). Hb and Ret were determined. A mixed model procedure was used to analyse the data. At baseline, Hb was similar for all groups, END showed lower Ret than NON-END and CON. Exercise showed a significant impact on Hb (+0.46 g/dl, p<0.001), the effect disappeared ~2 h after exercise. Hb decreased over the day by ~0.55 g/dl (p<0.01). There was no relevant effect on Ret. Fluid intake and ambient temperature had no significant effect. Hb shows significant diurnal- and exercise related variations. In an anti-doping context, most of these variations are in favour of the athlete. Blood samples taken after exercise might therefore provide reliable results and thus be used for the longitudinal monitoring of athletes if a timeframe for the re-equilibration of vascular volumes is respected.